Enhancing Learning Outcomes Through Neuropedagogy-Based Quantum Teaching - Rusydiana , Itsna (Journal of Education and Religious Studies, 2023)
This study aimed to analyze the effectiveness of applying Quantum Teaching methods based on neuropedagogy in enhancing student learning outcomes. Quantum Teaching is a pedagogical approach that integrated social, emotional, and cognitive elements within the learning process, while neuropedagogy focuses on understanding how the brain learned optimally. By integrating these two approaches, this study explored how a holistically designed learning environment facilitated the enhancement of students’ understanding and knowledge. The study conducted a mixed-method approach, utilizing both quantitative and qualitative methods to measure the impact of Quantum Teaching methods based on neuropedagogy on students’ academic performance. The findings indicated that students engaged in Quantum Teaching-based learning with a neuropedagogical approach experienced significant improvements in their learning outcomes compared to those following conventional teaching methods. Additionally, this study found that this approach positively affected students’ motivation, engagement, and the development of critical thinking skills. These findings contributed significantly to the field of education, particularly in the context of implementing innovative methods to enhance the quality of learning in the 21st century. The practical implications of this study included recommendations for developing more effective curricula and teaching strategies that educators could apply to achieve better and more holistic learning outcomes.